A nonlinear optimal control approach for the pulping process of paper mills. Issue 2 (4th April 2021) - Rigatos, G.; Abbaszadeh, M.; Cuccurullo, G.; Siano, P.
Abstract: The mechanical pulping process is non‐linear and multivariable. To solve the related control problem, the dynamic model of the pulping process undergoes first approximate linearization around a temporary operating point which is updated at each iteration of the control algorithm. The linearization process relies on first‐order Taylor series expansion and on the computation of the Jacobian matrices of the state‐space model of the pulping process. For the approximately linearized description of the pulping process, a stabilizing H‐infinity feedback controller is designed. To compute the controller's feedback gains, an algebraic Riccati equation is solved at each time‐step of the control method. The stability properties of the control scheme are proven through Lyapunov analysis.